2011
DOI: 10.1088/0029-5515/51/5/053002
|View full text |Cite
|
Sign up to set email alerts
|

Main chamber sources and edge transport of tungsten in H-mode plasmas at ASDEX Upgrade

Abstract: Abstract. In the fully tungsten clad ASDEX Upgrade, the sputtering rates of tungsten have been determined at all relevant plasma facing components using fast spectroscopic measurements with temporal resolution down to 0.5 ms. The sputtering strongly increases during an edge-localised mode (ELM) and the ELMs are often the dominant cause for tungsten sputtering. A modelling approach was employed to calculate the tungsten source at the limiters and the resulting tungsten density at the pedestal top inside of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(111 citation statements)
references
References 33 publications
3
108
0
Order By: Relevance
“…In an H-mode, the edge transport barrier provides a zone of good confinement, and the inward transport of tungsten is regulated by the ELMs. Thus, a higher ELM frequency is beneficial for reducing the tungsten concentration [3]. The ELM frequency increases with the amount of additional heating, the edge q 95 and the applied gas puff level.…”
Section: Comparison Of Iphm In the All-w Aug With Results From Previomentioning
confidence: 99%
“…In an H-mode, the edge transport barrier provides a zone of good confinement, and the inward transport of tungsten is regulated by the ELMs. Thus, a higher ELM frequency is beneficial for reducing the tungsten concentration [3]. The ELM frequency increases with the amount of additional heating, the edge q 95 and the applied gas puff level.…”
Section: Comparison Of Iphm In the All-w Aug With Results From Previomentioning
confidence: 99%
“…It is clear that by increasing the gas puff level not only the ELM frequency changes, but also the erosion source in the divertor during as well as in-between the ELMs. Furthermore there is a reduction of the ionisation length as well as an increase of the prompt redeposition of W + ions, calling for a consistent modelling, which is provided in [41]. In the frame of the ongoing melting experiments performed with dedicated melt probes in the divertor [44,45] the divertor retention has been reassessed using the 3D transport code EMC-3 [46].…”
Section: W Transport and Contentmentioning
confidence: 96%
“…If the W content is high enough it can even influence the transport in the background plasma by changing the electron temperature profile through the radiation losses. For keeping the overall W content in H-Modes low it is essential to provide an edge instability which regularly diminishes the large edge impurity density gradient due to neoclassical effects [41]. The flushing could be provided by natural or stimulated ELMs [42,34] or by a change in the edge transport by magnetic perturbation coils [2].…”
Section: W Transport and Contentmentioning
confidence: 99%
“…In general, no disruption occurred if the auxiliary heating was maintained, whereas switching off the NBI power in such a case could lead to disruption by radiation collapse event. The increase of the NBI power combined with strong deuterium gas puffing rate (above 10 22 Ds −1 ) opened up the operating space by increasing central transport and the ELM frequency and therefore the flushing out tungsten from the bulk plasma (see also Sec.3.4), as seen in AUG [42,43]. Since both the increase of the loss power (power crossing the separatrix) and the gas puffing contribute to expell tungsten by increasing the ELM frequency, it was also found that the minimum gas puffing rate decreases with the loss power.…”
Section: Baseline H-mode Scenariomentioning
confidence: 99%